Die Macht der Algorithmen - Grundmann, Thomas; Hey, Johanna; Hobe, Stephan; Katzenmeier, Christian; Körber, Torsten; Neuefeind, Claes; Ogorek, Markus; Rostalski, Frauke; Waßmer, Martin Paul (Schriften zu Recht und Ethik der Digitalen Transformation, 2023)
This volume contains seven lectures held at the University of Cologne in the winter semester of 2021/22 and the summer semester of 2022 as part of a lecture series organised by the Research Unit "Law and Ethics of Digital Transformation" under the general heading "The Power of Algorithms". The lectures deal with both basic questions and current issues of the digital transformation. The authors have been working on forward-looking topics for many years. With contributions by Nina Eckertz | Prof. Dr. Øyvind Eide | Prof. Dr. Dr. h.c. Dr. h.c. Stephan Hobe, LL.M. (McGill) | Dr. Amina Hoppe | Prof. Dr. Christian Katzenmeier | Prof. Dr. Torsten Körber, LL.M. | Prof. Dr. Axel Ockenfels | AkadR a.Z. Dr. Martin Schwamborn | Prof. Dr. Dr. h.c. Martin Paul Waßmer